Comparative transcriptome and histological analyses provide insights into the skin pigmentation in Minxian black fur sheep (Ovis aries) - Shi, Xiaolei; Wu, Jianping; Lang, Xia; Wang, Cailian; Bai, Yan; Riley, David Greg; Liu, Lishan; Ma, Xiaoming (PeerJ (San Francisco, CA), 2021)
Minxian black fur (MBF) sheep are found in the northwestern parts of China. These sheep have developed several special traits. Skin color is a phenotype subject to strong natural selection and diverse skin colors are likely a consequence of differences in gene regulation. Skin structure, color differences, and gene expression (determined by RNA sequencing) were evaluated the Minxian black fur and Small-tail Han sheep ( = 3 each group), which are both native Chinese sheep breeds. Small-tail Han sheep have a thicker skin and dermis than the Minxian black fur sheep ( < 0.01); however, the quantity of melanin granules is greater ( < 0.01) in Minxian black fur sheep with a more extensive distribution in skin tissue and hair follicles. One hundred thirty-three differentially expressed genes were significantly associated with 37 ontological terms and two critical KEGG pathways for pigmentation ("tyrosine metabolism" and "melanogenesis" pathways). Important genes from those pathways with known involvement in pigmentation included ( ), ( ), ( ) and ( ), ( ), and ( ). The results from our histological and transcriptome analyses will form a foundation for additional investigation into the genetic basis and regulation of pigmentation in these sheep breeds.